Preliminary Report on Prevalence of Intestinal Ciliate (Buxtonella sulcata) in Cattle of Assam - Das, M.; Deka, D. K. (Indian Journal of Hill Farming, 2018)
Buxtonella sulcata is an intestinal ciliate protozoon which inhabits the caecum of cattle. In neonates and immunocompromised calves it multiplies fast, become virulent and cause clinical disease. A total of 2339 fecal samples of calves (535), heifer (641) and adult (1163) cattle were screened for 1 year present in and around Guwahati, Assam for detection of B. sulcata infection by direct, sedimentation and formalin ethyl ether concentration methods. Examination of fecal samples revealed an overall prevalence of 0.81%infection of B. sulcata in dairy cattle. Age-wise, 0.74%, 0.78% and 0.85% infections of B. sulcata were recorded in calves (<1 year), heifer (1-3 years) and adult (>3 years) cattle, respectively. Strongyle sp., Eimeria sp., Amphistome, Strongyloides sp., Moniezia sp., Toxocara vitulorum, Trichuris sp., Fasciola gigantica and Bunostomum sp. were also recorded. This report may be considered as the first report of B. sulcata infection in cattle of Assam.